Effects of poultry fat and choice white grease on pork longissimus muscle, belly, and bacon quality - J J Engel; J W Smith II; Robert D Goodband; John A Unruh; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1998)
Eighty-four crossbred gilts were used to examine the effects of increasing dietary additions of poultry fat (PF) or choice white grease (CWG) on longissimus muscle (LM), belly, and bacon quality. Pigs fed PF had greater LM cooking loss values than those fed CWG. As PF increased in the diet, LM Minolta L* and belly lean values decreased. then increased. Neither fat source nor level significantly affected other LM quality or sensory traits. As PF increased, bacon slicing score decreased. Although all taste panel scores were well within acceptable ranges, bacon from pigs fed PF had higher sensory panel "off flavor" scores than bacon from those fed CWG. These data indicate that PF and CWG can be added to finishing pig diets with minimal affects on LM, belly, and bacon quality.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Pork; Dietary fat; Longissimus muscle quality